The Effect of Body Mass Index on the Outcome of Critically Ill Surgical Patients. Issue 3 (26th September 2012) - Gupta, Rajeev; Villa, Manuel; Agaba, Emanuel; Ritter, Garry; Sison, Cristina; Marini, Corrado P.; Barrera, Rafael
Abstract : Background : The incidence of obesity is rising, and an increasing number of obese patients are admitted to surgical intensive care units (SICUs). However, it is not clear whether obesity is an independent risk factor for increased morbidity and mortality in SICU patients. We examined the effect of obesity on morbidity and mortality in patients admitted to the SICU in this study. Method : We reviewed prospectively acquired SICU data in normal and obese patients with an SICU length of stay >24 hours. Comparability of the groups was assessed using a χ 2 test or Fisher exact test, as appropriate, for categorical variables and analysis of variance (ANOVA) or the Kruskal‐Wallis test, as appropriate, for continuous variables. Results : Of the 1792 consecutive patients evaluated, 711 had a normal body mass index (BMI), and 993 were either preobese or obese. There was no statistically significant difference across the 5 BMI groups with respect to any of the 3 comorbidity indices (Acute Physiology and Chronic Health Evaluation III [APACHE III], Simplified Acute Physiology Score, or Multiple Organ Dysfunction Score). There was no statistically significant difference in the intensive care unit (ICU) length of stay and hospital length of stay or time‐to‐ICU mortality (log‐rank test P = .054) among the 5 BMI groups. A Cox regression analysis and backward elimination algorithm selected APACHE III to be the most important explanatory variable for survival time. Conclusion : Obesity does not affect the mortality of patients admitted to the SICU. We conclude that obesity cannot be used as an independent predictive mortality outcome variable in patients admitted to the SICU.